INOVASI KUKU PALSU BERBAHAN LIMBAH KULIT SINGKONG (Manihot Esculenta) : SOLUSI KREATIF UNTUK KECANTIKAN RAMAH LINGKUNGAN - Mayustina Widyana; Anik Maghfiroh (Beauty and Beauty Health Education, 2025)
This study aims to examine the level of attractiveness and consumer acceptance of fake nail innovations made from cassava peel waste (Manihot esculenta) as a creative solution for environmentally friendly beauty products. The research method employed was descriptive quantitative, utilizing a five-point Likert scale questionnaire. The research sample consisted of 23 respondents selected purposively. Assessments were based on four main indicators: aesthetics, texture, eco-friendly appeal, and acceptance of innovative products. Data were analyzed using descriptive statistics to obtain mean scores and interpret rating categories.